Simultaneous construction of two linkages for the on-surface synthesis of imine–boroxine hybrid covalent organic frameworks. Issue 3 (12th December 2016) - Yue, Jie-Yu; Mo, Yi-Ping; Li, Shu-Ying; Dong, Wei-Long; Chen, Ting; Wang, Dong
Abstract : The orthogonality between the Schiff base reaction and the boronic acid dehydration reaction is explored during the on-surface synthesis process. Abstract : The orthogonality between the Schiff base reaction and the boronic acid dehydration reaction is explored during the on-surface synthesis process. By activating the above two reactions in one-step and employing asymmetrical substituted monomers and the 3-fold symmetric monomer 1, 3, 5-tris(4-aminophenyl)benzene (TAPB), highly ordered imine–boroxine hybrid single-layered covalent organic frameworks (sCOFs) have been successfully constructed on HOPG by a gas–solid interface reaction method and characterized by scanning tunnelling microscopy (STM). In particular, the reaction between the meta -substituted monomer and TAPB generates sCOFB with a windmill structure, which is the first sCOF with surface chirality so far reported. The demonstration of the one-step synthesis of multiple linkages to form sCOFs can further enlarge the sCOF family and expand the design routes for functional 2D organic nanomaterials.